PEMERIKSAAN VIRUS DENGUE-3 PADA NYAMUK Aedes aegypti YANG DIINFEKSI SECARA INTRATHORAKAL DENGAN TEKNIK IMUNOSITOKIMIA MENGGUNAKAN ANTIBODI DSSE10 - Dyah Widiastuti; Sitti Rahmah Umniyati; Nastiti Wijayanti (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2012)
Dengue viruses, globally the most prevalent arboviruses, are transmitted to humans by persistently infected Aedes mosquitoes. The most important vector of Dengue virus is the mosquito Ae.aegypti, which should be the main target of surveillance and control activities. Virologic surveillance for dengue viruses in its vector has been used as an early warning system to predict outbreaks. Detection of Dengue virus antigen in mosquito head squash using immunocytochemical streptavidin biotin peroxidase complex (SBPC) assay is an alternative method for dengue vector surveillance. The study aimed to develope immunocytochemical SBPC assay to detect Dengue virus infection in head squash of Ae.aegypti. The study design was experimental. Artificially-infected adult Ae. aegypti mosquitoes of DENV 3 were used as infectious samples and non-infected adult Ae. aegypti mosquitoes were used as normal ones. The immunocytochemical SBPC assay using monoclonal antibody DSSE10 then was applied in mosquito head squash to detect Dengue virus antigen. The results were analyzed by descriptive analysis. The immunocytochemical SBPC assay can detect Dengue virus antigen in mosquito head squash at day 2 postinfection. There are some false positive results found in immunocytochemical SBPC assay.